BELLA SWAN’S BORDERLINE PERSONALITY DISORDER AS ARESULT OF THE ABSENCE OF MATERNAL CARE IN STEPHENIE MEYER’S TWILIGHT SAGA - Seruni Arifa (LINGUA LITERA : journal of english linguistics and literature, 2022)
Abstract Mental disorders are common in modern times. It can be seen in the novel Stephanie Meyer’s Twilight Saga. It describes that the main character has a psychological problem. As a result of her failed expectations about her mother's figure, she experienced early trauma and disappointment, which culminated in mental changes that led to Borderline Personality Disorder. Two problems are proposed in this research; how does the absence of maternal care trigger mental disorders and the impact of Borderline Personality Disorder suffered by BellaSwan. This research uses the theory of Object Relations by Otto F. Kernberg. Two of Kernberg’s concepts are considered appropriate to be utilized: mother-daughter relationships and the concept of Borderline Personality Disorder. Those concepts help this research to describehow the absence of maternal care trigger mental disorder and the kind of Borderline Personality Disorder suffered by Bella Swan. The result of this research shows two main points. First, the absence of maternal care is the cause of the failure of character-forming and it led to Borderline Personality Disorder. Second, the impact is shown through her being unconfident and split up from the social.